Everyday actions in science teaching: a case study in public and private schools (Research, Society and Development, 2022)
Science teaching has been guided by different trends that are still used in the classroom today. More recently, the concern with developing experimental activities began to have a strong presence in teaching projects and teacher training courses. In the municipality of Abaetetuba-PA, located in the Amazon, most education professionals do not pay attention to the fact that everyday situations are directly linked to scientific knowledge. This article was intended to approach methodological actions of everyday life at school, seeking support in the empirical knowledge of students so that they can use the academic knowledge acquired in the classroom to understand and solve problems of daily life. The socioeconomic characteristics of the students were analyzed and ten experiments in the area of science were related to daily life, to the syllabus, and applied to 60 students from the 4th grade of an elementary school in the municipal education network (public) and in a private school. All experiments applied with this methodology had widespread acceptance among students and proved to be effective in students' performance. Through the ANOVA calculation, it was found that there were no significant differences for most of the answers between the students of the two schools.